2011
DOI: 10.1029/2011jd016674
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble organic aerosol in the Los Angeles Basin and outflow regions: Airborne and ground measurements during the 2010 CalNex field campaign

Abstract: [1] A particle-into-liquid sampler coupled to a total organic carbon analyzer (PILS-TOC) quantified particulate water-soluble organic carbon (WSOC) mass concentrations during the May 2010 deployment of the Center for Interdisciplinary Remotely Piloted Aircraft Studies (CIRPAS) Twin Otter in the CalNex field study. WSOC data collected during 16 flights provide the first spatiotemporal maps of WSOC in the San Joaquin Valley, Los Angeles Basin, and outflow regions of the Basin. WSOC was consistently higher in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 68 publications
3
60
0
Order By: Relevance
“…It was found that the ML height can vary by large amounts, up to as much as 2 km, in locations surrounding the ceilometer. This is likely due to variations of ML heights with the complex terrain, differing meteorological conditions over the ocean and mountains, and the transport of pollutants within the study region (Duong et al, 2011). Repeating the comparison between HSRL and ceilometer ML heights, we see that the comparison breaks down quickly at separations beyond 30 km.…”
Section: Comparison With Ceilometer and Investigation Of Spatial Varimentioning
confidence: 90%
See 1 more Smart Citation
“…It was found that the ML height can vary by large amounts, up to as much as 2 km, in locations surrounding the ceilometer. This is likely due to variations of ML heights with the complex terrain, differing meteorological conditions over the ocean and mountains, and the transport of pollutants within the study region (Duong et al, 2011). Repeating the comparison between HSRL and ceilometer ML heights, we see that the comparison breaks down quickly at separations beyond 30 km.…”
Section: Comparison With Ceilometer and Investigation Of Spatial Varimentioning
confidence: 90%
“…The Los Angeles basin is bordered by the San Gabriel Mountains, the San Bernardino Mountains, and the Pacific Ocean. Duong et al (2011) discuss that the LA basin is impacted by sea breezes and mountain flows that can transport or trap aerosols. During CalNex, there were three aircraft outfitted with atmospheric measurement instruments, a research vessel also carrying atmospheric measurement instruments, and a suite of ground-based instruments (Ryerson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Chuang et al (2013b) have reported WSOC as high as 25.2% PM 2.5 in Chiangmai, Thailand. By contrast, Duong et al (2011) have reported relatively WSOC as low as 6%-11% of PM 2.5 in the Los Angeles Basin and outflow regions during the 2010 CalNex field campaign. Table 1 also shows WSOC in OC to be 62.8% ± 8.2% and 57.8% ± 15.5% in 2012 and 2013, respectively.…”
Section: Carbonaceous Contentsmentioning
confidence: 94%
“…Limits of detection were 0.2 and 1.0 µgm −3 for EC and OC, respectively. Water-soluble organic carbon (WSOC) was measured in PM 2.5 using a particle-into-liquid sampler (PILS, Brechtel Manufacturing Inc.) coupled to a total organic carbon analyzer (TOC; Sievers model 800) (Sullivan et al, 2006; Duong et al, 2011; Wonaschütz et al, 2011). The overall measurement uncertainty associated with the reported WSOC concentrations is estimated to be approximately 10% with a limit of detection of 0.1 µgm −3 .…”
Section: Methodsmentioning
confidence: 99%